2019
DOI: 10.1038/s41380-019-0364-x
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Full recovery of the Alzheimer’s disease phenotype by gain of function of vacuolar protein sorting 35

Abstract: Deficit in retromer complex function secondary to lower levels of one of its major components, the vacuolar protein sorting 35 (VPS35), has been reported in Alzheimer’s disease (AD) brains. VPS35 genetic reduction results in increased Aβ levels and synaptic pathology in mouse models of the disease. However, whether restoration of its levels has an effect on the AD-like phenotype which includes Aβ plaques, tau tangles and memory impairments remains unknown. In this paper, we investigated the effect of VPS35 gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
56
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

4
4

Authors

Journals

citations
Cited by 50 publications
(62 citation statements)
references
References 38 publications
6
56
0
Order By: Relevance
“…Despite concerns raised about non-physiological overexpression of multiple mutations in three different genes linked to AD and to FTD, this mouse has proven extremely useful to model the consequences of aggressive amyloid and tau pathology in the context of autosomal-dominant disease 2426 . Our findings compliment this prior study 23 , by not only investigating a mouse that is genetically simpler -- depleting a single endogenous gene -- but by using a model that better reflects ‘sporadic’ late-onset AD.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Despite concerns raised about non-physiological overexpression of multiple mutations in three different genes linked to AD and to FTD, this mouse has proven extremely useful to model the consequences of aggressive amyloid and tau pathology in the context of autosomal-dominant disease 2426 . Our findings compliment this prior study 23 , by not only investigating a mouse that is genetically simpler -- depleting a single endogenous gene -- but by using a model that better reflects ‘sporadic’ late-onset AD.…”
Section: Discussionsupporting
confidence: 87%
“…A recent study showed that viral vector delivery of VPS35 to a neonatal triple-transgenic mouse model rescued defects induced by amyloid and tau pathology 23 . These genetically complex mice overexpress two human mutations in APP and a mutation in presenilin1 (PSEN1), each a cause of autosomal-dominant AD; and, overexpresses a human mutation in the microtubule associated protein tau (MAPT) that is a cause of fronto-temporal degeneration (FTD).…”
Section: Discussionmentioning
confidence: 99%
“…Besides the experimental evidences from transgenic mice and that Bcl6 and Stat3 regulate M1 genes, as mentioned in the Results. We also found 21 of the AD1 genes are Stat3 upstream regulators, eight of which have been shown recently shown to involve in AD pathology in transgenic mouse model studies (MAPK1 (Du et al, 2019), RHEB (Shahani et al, 2014), SUMO1 (Knock et al, 2018), VPS35 (Li et al, 2019), GSK3B (Llorens-Martin et al, 2017), DYRK1A (Branca et al, 2017), EPHA4 Fu et al, 2014) Although we observed overall decreased expression of neuron modules which was consistent with the neuron loss in AD brains (Srinivasan et al, 2016), to our surprise, we also detected an increment in overall co-expression level of the neuron modules in AD brains across all five datasets, which is a new discovery. This increased correlation in the neuron module may be linked to the neuronal hyperactivity in AD previously observed in both human and mouse models (Stargardt et al, 2015).…”
Section: Discussionsupporting
confidence: 66%
“…We found that the Parkinson's Disease-modeling Vps35 D628N mutant does not recapitulate the EV trafficking defects arising from deletion of Vps35, suggesting that EVs may not play a primary role in patients with this mutation. Instead, our results in the Vps35 deletion mutant may relate more directly to Alzheimer's Disease, which is tightly associated with reduced overall levels of retromer based on genetic and pathological data from patients (Small et al, 2005;Vardarajan et al, 2012) as well as more severe pathology in Vps35-depleted animal models, including Drosophila (Li et al, 2019;Muhammad et al, 2008;Wen et al, 2011). The specific role of retromer in APP traffic has remained unclear, because of differing results in various cell types regarding the normal trafficking itineraries and points of intersection for APP and its processing proteases, as well as the effects of retromer loss on these trafficking patterns (Bhalla et al, 2012;Brodin and Shupliakov, 2018;Choy et al, 2012;Cuartero et al, 2012;Das et al, 2013;Das et al, 2016;Fjorback et al, 2012;Li et al, 2012;Sullivan et al, 2011;Tan and Gleeson, 2019;Toh et al, 2017;Vieira et al, 2010;Wang et al, 2012a;Wen et al, 2011).…”
Section: Role Of the Retromer-rab11 Ev Pathway In Neuronal Function Amentioning
confidence: 78%
“…Neuronal retromer localizes to cell bodies, dendrites, and axons, and is required for proper synaptic morphology, synaptic transmission, synaptic vesicle number, and AMPA receptor traffic (Bhalla et al, 2012;Choy et al, 2014;Inoshita et al, 2017;Korolchuk et al, 2007;Munsie et al, 2015;Temkin et al, 2017;Tian et al, 2015;Vazquez-Sanchez et al, 2018;Wu et al, 2017). In cellular and animal models of Alzheimer's Disease, loss of retromer exacerbates synaptic and cognitive defects, and causes mislocalization of APP as well as its amyloidogenic protease BACE1, ultimately leading to increased Ab (Bhalla et al, 2012;Choy et al, 2012;Eggert et al, 2018;Li et al, 2019;Muhammad et al, 2008;Sullivan et al, 2011;Tan and Gleeson, 2019;Wen et al, 2011). Retromer levels are reduced in the entorhinal cortex of Alzheimer's Disease patients (Small et al, 2005), and it has therefore been proposed as a therapeutic target (Berman et al, 2015;Mecozzi et al, 2014).…”
Section: Introductionmentioning
confidence: 99%